2015
DOI: 10.1007/978-1-4939-3353-2_13
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Calcification in Uremia: New-Age Concepts about an Old-Age Problem

Abstract: A hallmark of aging, and major contributor to the increased prevalence of cardiovascular disease in patients with chronic kidney disease (CKD), is the progressive structural and functional deterioration of the arteries and concomitant accrual of mineral. Vascular calcification (VC) was long viewed as a degenerative age-related pathology that resulted from the passive deposition of mineral in the extracellular matrix; however, since the discovery of "bone-related" protein expression in calcified atherosclerotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 212 publications
2
18
0
Order By: Relevance
“…Therefore, a model of TM phenotype was successfully reproduced in this study. Our results also confirmed that human NPs were the known agents of emerging infectious diseases and producing apatite, which agrees well with other reports [ 14 , 15 ]. A possible calcification mechanism might be NP colonization in seminiferous tubules inducing an immune response, promoting inflammation development and further calcification.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, a model of TM phenotype was successfully reproduced in this study. Our results also confirmed that human NPs were the known agents of emerging infectious diseases and producing apatite, which agrees well with other reports [ 14 , 15 ]. A possible calcification mechanism might be NP colonization in seminiferous tubules inducing an immune response, promoting inflammation development and further calcification.…”
Section: Discussionsupporting
confidence: 93%
“…VC, abnormal deposition of calcium-phosphate (Pi) salts in vascular tissues including blood vessels, valves, and heart, is frequently observed in aging, diabetes mellitus, CKD, calcific aortic valve disease (CAVD), and several genetic diseases [58]. Mounting clinical evidence has shown that VC is indeed an independent predictor of cardiovascular morbidity and mortality in CKD and ESKD [911].…”
Section: Cardiovascular Mortality and Vascular Calcification (Vc)mentioning
confidence: 99%
“…The formation of VC is associated with complex pathological mechanisms, including osteochondral differentiation and apoptosis of vascular smooth muscle cells (VSMCs), instability and release of extracellular vesicles loaded calcium and phosphate . Among the various causes in CKD, abnormal deposition of calcium phosphate (Pi) salt is most closely related to VC . It has been proved that elevated serum Pi is a risk factor for VC and cardiovascular mortality and morbidity among CKD populations in clinical studies .…”
Section: Introductionmentioning
confidence: 99%
“…1,7 Among the various causes in CKD, abnormal deposition of calcium phosphate (Pi) salt is most closely related to VC. 8 It has been proved that elevated serum Pi is a risk factor for VC and cardiovascular mortality and morbidity among CKD populations in clinical studies. 9,10 Therefore, it is of great significance to study the specific molecular mechanism of VSMCs calcification induced by high phosphorus in CKD.…”
Section: Introductionmentioning
confidence: 99%